Peter Doherty on the role of science supporting Africa's food production - Doherty, Peter F. (International Livestock Research Institute, 2016)
Peter Doherty, Nobel Prize Laureate for Physiology or Medicine–1996, and ILRI patron, speaks about Africa's potential in food production and the role of research and capacity development in supporting more productive agriculture. He emphasizes the opportunities for Africa to move from food imports to total food security, based on evidence based strategies. Filmed in September 2016.